The Effect of the Hepatitis B Vaccine Derived from Genotype C on Infants Born to Mothers Infected with Genotype D - Michitaka, Kojiro; Ohno, Naofumi; Hiasa, Yoichi; Watanabe, Takao; Tokumoto, Yoshio; Abe, Masanori; Yoshida, Osamu; Hiraoka, Atsushi; Ninomiya, Tomoyuki (Internal Medicine, 2020)
Objective There is a paucity of information on whether the hepatitis B virus (HBV) vaccine, derived from HBV genotype C, can prevent mother-to-child transmission of HBV genotype D. The aim of this study was to clarify this issue. Methods The subjects consisted of 25 children (8.5±4.1 years old, 7 males, 18 females), born to 17 mothers who were chronically infected with HBV genotype D. Of these, 20 children were inoculated with the genotype C-derived vaccine, one was inoculated with the genotype A-derived vaccine, and one was inoculated with both the A- and C-derived vaccines. Information on the type of vaccine given to the remaining three children was not available. The serum levels of HB surface antigen (HBsAg), antibody to HBsAg (anti-HBs), and antibody to HB core (anti-HBc) of the children, as well as HBV markers of the mothers, were examined. Results All mothers were positive for HBsAg (6,563±11,005 IU/mL), negative for HBeAg, and positive for anti-HBe. HBV-DNA levels (log IU/mL) were <3.3 in 7 mothers, 3.3-4.3 in 9 mothers, and >4.3 in one mother. HBsAg and anti-HBc were negative in all children, regardless of the type of vaccine used. Anti-HBs were positive in 13 children and negative in 12. Conclusion All children born to mothers infected with genotype D, including 20 who were inoculated with the genotype C-derived vaccine, were negative for both HBsAg and anti-HBc. These results suggest that the genotype C-derived HB vaccine is effective in preventing mother-to-child transmission from mothers infected with HBV genotype D.